Exotic fish culture in pond aquaculture system: Study of Rupchanda (Piaractus brachypomus) culture in Assam, India - Jyoti Prabhat Duarah; Manmohan Mall; Swapnali Chetia Phukan (Cogent Business & Management, 2023)
Exotic fish species are introduced in the pond culture system with a view to improving aquaculture development. Apart from aquaculture development, the introduction of exotic species has an undesirable impact on the natural biodiversity due to prolific breeding tendencies, predation or competition with the indigenous species. However, evidence of socio-economic benefits from a specified exotic species culture to fish farmers needs to be investigated properly. There are many more exotic species which have occupied their place in the composite pond aquaculture system in India and Assam in particular. In this work, an attempt was made to study the culture of Piaractus brachypomus (Local name Rupchanda) in the pond aquaculture system of Assam. Being a native species of South America also known as Rupchanda, it is often confused with Piranha (Pygocentrus nattereri). From this study, it was observed that in the fish market of Assam, this fish (Rupchanda) fetches less price as compared to Carps. It was also found that this species has a good growth rate, acceptance to a wide variety of feed and the ability to be stocked in higher stocking density in ponds as well as the volume of sale is higher vis-à-vis the Indian Major Carps. It reaches marketable size within four to five months making this fish species widely accepted for culture by the farmers of Assam and also there is a good volume of trade occurring for the seeds of P. brachypomus. In this regard, this research work is a novel attempt in analysing the economic benefits and challenges of adopting a controlled culture of P. brachypomus (Rupchanda) in the ponds of Assam.
Keywords: 650; crop intensification strategy; exotic fish; Indian major carps; Rupchanda (P. brachypomus); socio-economic development